Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1016/0014-5793(92)80508-e
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between ruptured erythrocytes and low‐density lipoproteins

Abstract: Low-density lipoproteins (LDL) are oxidatively modified on interaction with haem proteins. The interaction of ruptured erythrocytes with LDL induces oxidative damage as detected by alterations in electrophorctic mobility and the peroxidation of the polyunsaturated fatty acyl chains. Difference spectroscopy reveals that the amplification of the oxidative process by the hacm protein is related to the transition of [he oxidation state of the haemoglobin in the erythrocyte lysate from the oxy [x-Fei'-O1] to the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Besides classical reactive oxygen metabolites, organic peroxides were shown to induce the leakage of Hb from human erythrocytes [40] and the generation of metHb [41]. FerrylHb generation was detected in the interaction between ruptured erythrocytes and LDL [42, 43]. Parallel with these findings here we showed that oxLDL but not native LDL caused Hb oxidation and subsequent covalent crosslinking of Hb subunits (Figure 4.)…”
Section: Discussionsupporting
confidence: 81%
“…Besides classical reactive oxygen metabolites, organic peroxides were shown to induce the leakage of Hb from human erythrocytes [40] and the generation of metHb [41]. FerrylHb generation was detected in the interaction between ruptured erythrocytes and LDL [42, 43]. Parallel with these findings here we showed that oxLDL but not native LDL caused Hb oxidation and subsequent covalent crosslinking of Hb subunits (Figure 4.)…”
Section: Discussionsupporting
confidence: 81%
“…Most of them including our team have shared common findings of lowered total cholesterol, LDL-C, HDL-C [27, 34–39]. Values from our B-TM patients and many other researchers showed elevated triglyceride levels (TG) [33, 34, 36–38], while others described TG levels as being not- significantly different from controls [35, 39]. CAIMT in the present study was positively correlated with S. TG and atherogenic index of plasma.…”
Section: Discussionmentioning
confidence: 90%
“…Lipid profiles have been described by several investigators but with conflicting results [26, 33–36]. Most of them including our team have shared common findings of lowered total cholesterol, LDL-C, HDL-C [27, 34–39].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unlike free iron, solid indications point to excellular hemoglobin involvement in LDL oxidation and atherosclerosis ( , ). A positive correlation was demonstrated between elevated levels of oxidized LDL and intravascular rupture of erythrocytes in uremic patients undergoing hemodialysis who are prone to atherosclerosis ( ).…”
mentioning
confidence: 99%